Climatic zoning of conditions for the development of the larva of the mosquito that transmits the dengue fever virus in the State of Rio Grande do Sul - Buriol, Galileo Adelii (2015)
Climatic zoning was carried out in the State of Rio Grande do Sul for the development of the larva of the mosquito that transmits the dengue fever virus, Aedes aegypti. The study used the average and the variability of the total monthly precipitation, the average number of days per ten day-periods with precipitation, the monthly average temperature charts of medium, maximum, and minimum temperatures, and the probability of occurrence of absolute minimum temperatures below 5°C. The study considered as preferable those regions with average temperature between 24 and 32°C; as tolerable those between 18 and 24°C; as marginal those between 5 and 18°C; and as unsuitable those below 5°C and above 40°C. It verified that hydric conditions in Rio Grande do Sul throughout the year are suitable for the development of the larva of the mosquito transmitter of the dengue virus fever, and that the most suitable thermal availabilities occur during the months of January, February, and December. The most suitable average temperatures occur mainly in the Climatic Regions of the Central Depression, High and Low Uruguayan Valley and Missions; whereas the marginal ones occur in the Northeastern Mountains, West of the Uplands, Southeastern Mountains, and Southern Shore.